Activity of Bamboo Wulung’s Smoke Gigantochloa atroviolace againts Subterranean Termites and Fungi Attack - Subekti, Niken; Yoshimura, Tsuyoshi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2020)
Termites are plants, housing, furniture, and building pests. Termite control has been carried out using synthetic pesticides that are harmful to the environment and human health. Innovation in controlling termites and fungi is required for the preservation of wood and furniture. The aim of this study was to analyze the use of bamboo Wulung’s (Gigochocha atroviolace) smoke for controlling termites and fungi attacks. The methods used were the manufacture of bamboo’s smoke, a test of preference for termites, and mortality of termites. The results showed that liquid smoke at 450oC was effective for controlling termites and fungi. The smoke of bamboo Wulung with a concentration of 10% can control C. formosanus termites. It showed 100% mortality within 14 days, while the smoke of bamboo Wulung with a concentration of 5% showed 100% mortality of R. speratus within 14 days. Bamboo smoke at pyrolysis temperature 450oC and a concentration of 2.0% can prevent the growth of T. vesicolor fungus while effective at the same concentration for F. palustris. Bamboo smoke can prevent the growth of T. vesicolor mushrooms at a liquid smoke temperature of 450oC with a concentration of 2% and the fungus F. palustris at a concentration of 2.0%.